An Analysis of the Meaning of Apem in Java: Semiotics Analysis - Resta, Tiara (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to analyze how language is closely related to culture and cannot be separated. It is the same in the Java region that uses traditional apem to make the early generations to the present generation continue to use the tradition (apem which is used as main food in several events). Method that already used in analyzing this research is descriptive and the writer trying to describe the subject or object being studied in more depth and then interpret it. Result of the research that the writer has done is getting deeper into the meaning of apem in Javanese society and the knowledge of this tradition will always be given to new generations who in the future will continue to recognize the meaning contained in the apem.